Role of affect in marketplace rumor propagation. Issue 6 (2nd September 2019) - Sudhir, Subin; Unnithan, Anandakuttan B.
Abstract : Purpose: Rumors about products and brands are common occurrence in the marketplace. Often these rumors are shared among consumers using the word of mouth channel. The spread of these rumors is fast and can lead to significant consequences to products and brands. The purpose of this paper is to explore the dynamics of such rumor sharing behavior among consumers. Specifically, this paper investigates the role of positive affect and negative affect in rumor sharing behavior. Three key rumor characteristics (valence, involvement and credibility) are explored as antecedents to positive affect and negative affect. Design/methodology/approach: The paper collects data from 236 respondents using Amazon MTurk, and conducts a PLS–SEM analysis to explore the role of positive affect and negative affect in rumor sharing contexts. Findings: Both positive affect and negative affect were found to be significant factors leading to rumor sharing, furthermore positive affect was found to have a stronger influence on rumor sharing as compared to negative affect. The study also delineates the role of valence, involvement and credibility in rumor sharing scenarios, all of which have a strong role in shaping positive affect and negative affect. Originality/value: The study is novel in using cognitive appraisal theory to illustrate the formation of positive affect and negative affect in rumor encounters. The study conclusively illustrates the role of cognitive appraisal and emotional experiences in the rumor propagation context, and advances the marketing scholarship's understanding significantly.